Industry 5.0 and green supply chain management synergy for sustainable development in Bangladeshi RMG industries - Md Al Amin; Arka Chakraborty; Roberto Baldacci (Cleaner Logistics and Supply Chain)
The conjugation of environment and technology coerced the industry to combine these two instruments towards a sustainable and resilient future. Industry 5.0 is the most recent infrastructural revolution of industrial sector technology based on technologies like human–machine interaction, artificial intelligence, IoT, Big Data, collaborative robots, etc. This happened when the sector radically turned its global focus to sustainability and set many environmental goals to meet the requirements. In this research, the authors identified the synergy between Industry 5.0 and green supply chain management (GSCM) for achieving this target at RMG industries in Bangladesh. GSCM is well known for environmental concerns in traditional supply chain stages. For developing countries, the solution of a sustainable approach to counter waste and pollution-related issues is not adequate enough. A proper understanding of the digitalized industrial approach through Industry 5.0 will enable them to make efficient decisions regarding sustainable goal accomplishment and proper monitoring of the initiatives. This paper illustrates how I5.0 can integrate with GSCM. In this synergy, this study has identified 9 synergistic factors and analyzed the impact of each factor by using the interpretive structural modeling approach. By using level portioning, the factors are illustrated in 7 different levels, and MICMAC analysis is used to categorize them. This study offers a detailed exploration of the synergy between Industry 5.0 and GSCM, offering a practical framework that can guide industry stakeholders in implementing advanced technologies to achieve sustainable development in the RMG sector.